Health Insurance and Child Health: Evidence from Mexico - Gabriella Conti; Rita Ginja (Institute for the Study of Labor (IZA), 2016)
We present evidence on the health impacts and mechanisms of a large expansion in non-contributory health insurance in Mexico. The Seguro Popular (SP) was rolled out in 2002-2010 across municipalities, providing exogenous variation in access to health services without co-pays. Our intent-to-treat estimates show that SP reduced child mortality by 7% in poor municipalities, saving 861 children/year. The decline is driven mainly by deaths due to preventable causes, such as diarrhea and respiratory infections. We also document an increase in hospital care for children with the same conditions. Our findings have important implications for the ongoing health insurance expansions.
Keywords: H10; I12; I13; J13; O18; 330; health insurance; child mortality; health care utilization; Mexico